THE TRAJECTORY OF THE DISCOURSE OF JIHAD IN INDONESIA - Taufiqur Rahman (Analisa: Journal of Social Science and Religion, 2016)
The term jihad is central in the development of Islamic identity and the political usage. The term has created many competing identities within Muslim communities especially in Indonesia, a country with the biggest Muslim population in the world. This article provides a historical analysis of the representation of the term jihad in the writing of Muslim scholars and organizations in Indonesia from the early arrival of Islam to the contemporary debate in the context of democratic transition after the collapse of Soeharto’s authoritarian regime. This article employs discourse analytical tools to look at various interpretations of the concept of jihad in the global context and particularly in the Indonesian context, and how these global and local interpretations are interconnected. The article argues that the doctrine of jihad in the history of Islam has developed into a contested doctrine over a long period of time. The article suggests that there is a long history of substantial minorities promoting militaristic jihad in Indonesia against ‘enemies’ of Islam which are defined variously from colonial state to the Indonesian government. The promotion of militaristic jihad was undermined by the consensus of mainstream moderate and peaceful Islam developed in the middle to late years of the New Order regime. However, the promotion of militaristic jihad reappeared after the fall of the New Order authoritarian regime and was further reinforced by transnational influences.